How does reserve capacity influence transition into upper secondary school among adolescent Finns? - Koivusilta, Leena Kristiina (Archīum Ateneo, 2020)
Background Educational inequalities occur when differences in educational outcomes are more strongly related to students' background than their own academic efforts. During adolescence, psychosocial resources such as social support and self-efficacy, collectively termed “reserve capacity” may serve as a pathway to educational transitions and help reduce educational inequalities. We study how reserve capacity affects transition of adolescents into upper secondary school in terms of non-placement or placement into vocational or academic track. Methods We use data from 9th graders in 128 schools at the 14 municipalities of Helsinki Metropolitan region who participated in the MetLoFin follow-up survey in 2014 (n = 7,344 students). The data were linked with the national Joint Application Registry containing information on whether student was placed in academic (65%) or vocational (32%) track or had no placement (3%) for upper secondary schools. Multinomial logistic regression models, adjusted for sex and school, were fitted to analyse the effect of students' background and reserve capacity on type of educational placement. Results Students whose parents had low education were more likely to be in vocational than academic track compared to those whose parents had high education (OR = 2.5 95% CI: 2.1-3.0). Having a foreign background increased the risk of having no placement than academic placement (OR = 1.5 95% CI: 1.1-2.2) compared to native students. Low social support and low self-efficacy predicted vocational placement of students relative to academic track but not no placement compared to academic placement. Academic grades remained strongest predictor of placement. Conclusions Students' background still determine educational outcomes, but psychosocial resources could likely reduce educational inequalities and ensure successful educational transitions in adolescence.